Expressão heteróloga e caracterização funcional da proteína Atx1 em Paracoccidioides spp - Morais, Camila Oliveira Barbosa de (2018)
Paracoccidioidomycosis (PCM) is an important mycosis of Latin America, caused by thermodymorphic fungi of the genus Paracoccidioides. Homeostasis of metals such as copper, zinc and iron is important for the survival of fungi in the host environment. In this context, copper is an important cofactor for several enzymes, such as as superoxide dismutases and cytochrome c oxidase. The excess free copper in the cell promotes accumulation of reactive oxygen species, causing damage to nucleic acids, lipids and proteins. Thus, organisms shall to maintain cytoplasmic levels of that micronutrient at non-toxic levels, just sufficient for cell growth and vital metabolic processes. The metabolism of that metal is strictly controlled by high and low affinity uptake systems. The objective of this work is to perform heterologous expression of the Atx1 protein, described in the literature as a copper chaperone, and to analyze its cellular location, as well as the protein behavior upon copper deprivation in Paracoccidioides spp. Heterologous expression was performed on electrocompetent cells of Escherichia coli strain BL21. Identity of the recombinant protein was confirmed by LC-MS / MS. BALB/c mice were immunized to obtain anti-Atx1 polyclonal antibodies. After performing immunoblotting the produced antibodies were used in immunofluorescence assays. Analysis by qRT-PCR allowed us to evaluate the levels of the transcript encoding the Atx1 protein during copper deprivation in Paracoccidioides spp.